Wild dogs : the natural history of the non-domestic Canidae - Sheldon, Jennifer W. (Academic Press, 1992)
Wild Dogs: The Natural History of the Nondomestic Canidae presents a comprehensive, current natural history of the nondomestic dog species. In this book, a prodigious amount of previously uncollected information is presented in a straightforward form. The organization of the book is alphabetical by genus, and, within each genus, alphabetically by Linnean species name. In some cases, very little is known about a species. In other cases, the amount of available information is enormous, and has been distilled to summary form. The volume is intended as a straightforward assemblage of material. It.